A Study of the Implementation of the Discovery Learning Model on the Speaking Skills of Class VIII Students at Madrasah Tsanawiyah Darul Ulum Sasa Ternate City - S Syamsia; Siska Febrianti Udin (Jurnal Langua, 2022)
The aims of this research are to find out the percentage of students' speaking skills complete before and after using the discovery learning model at the students of Madrasah Tsanawiyah Darul Ulum Sasa and to find out whether the discovery learning model is effective in improving students' speaking skills or not. This research is descriptive in nature which aims to describe or describe the percentage of mastery values ​​of speaking skills before and after the use of the discovery learning learning model. The method used in this research is an experimental method of Quasi Experimental Research with a research design of "One Groups Pretest-Posttest Design". The result of the percentage of students' mastery speaking skills value is very high after the application of the discovery learning learning model is 97,96% compared to the percentage of students' speaking skills mastery scores before the implementation of the discovery learning learning model is 100% incomplete. The average value of the students' speaking skills after the application of the discovery learning model is 84,41 was higher than the average value of the students' speaking skills before the application of the learning model is 53,47. There is a relationship between the students' speaking skills scores before (pretest) and after (posttest) the application of the discovery learning learning model is 55.2%. The percentage of the effectiveness of the application of the discovery learning learning model in increasing the value of students' speaking skills is 66.95% or the Quite Effective category.